Spirulina - From growth to nutritional product: A review - Soni, Ruma Arora; K., Sudhakar; Rana, R. S. (Elsevier Ltd, 2017)
Spirulina is multicellular and filamentous cyanobacteria that have achieved a considerable popularity in the health sector, food industry and aquacultures. It develops and grows in water, can be harvested and processed easily. It has very high content of macro and micronutrients, essential amino acids, proteins, lipids, vitamins, minerals and anti-oxidants. Spirulina is considered as a complete food supplement to fight against malnutritional deficiencies in developing countries. Spirulina is deemed safe for human consumption as evident by its long history of food use and latest scientific findings. In recent years, Spirulina has gathered enormous attention from research fraternity as well as industries as a flourishing source of nutraceutical and pharmaceuticals.